The age problem and growing of structures for open system cosmology - Campos,M. de (2001)
A new equation for the density contrast is derived in the framework of reexamined Newtonian cosmology if we take into account adiabatic matter creation in the universe. The age of the universe and the reach of non linear regime of the density contrast are usually treated separately in the literature and this may leadtocontroversial conclusions regarding the most adequate scenario to describe the universe. We relate the age of the universe and the growing mode of the density contrast by introducing a variable x that relates both of them, so that both aspects are treated simultaneously. We apply this procedure to the Friedmann type model where the source of particle production is Y = 3nbH.